Comparison of National State-Owned Enterprise and Global Company: Case Study of Efficiency in Fertilizer Producers - Maslani; Hartoyo; Rizal Syarief; Harianto (Jurnal Manajemen & Agribisnis, 2023)
Efficiency for fertilizer producers is critical in facing national and global competition. This study compares the efficiency of national fertilizer producing State-Owned Enterprises (SOE) companies with global fertilizer companies in different market structures. This research uses purposive sampling, namely world fertilizer producers (based on the top 10 in revenue or net profit) and SOE producers. This quantitative research uses the Data Envelopment Analysis (DEA) method on national and global companies from 2015 to 2021. The research results show that no national fertilizer producer was efficient compared to all global producers in the research period. It shows that the domestic oligopoly market structure tends to be inefficient compared to the global perfect competition market structure. Efficient global companies, including CF Industries, PhosAgro, Yara International, Sinofert, and Nutrien, can be used as benchmarks for national companies to increase their competitiveness. When we compare the efficiency among national companies, Petrokimia Gresik (PKG) and Pupuk Kalimantan Timur (PKT) are efficient. The inequality/disparity in efficiency at the national and global level is relatively high, so it is necessary to take strategies such as guaranteeing the availability of fertilizer raw materials in the long term, controlling market share, revitalizing more efficient fertilizer factories, and optimizing the supply chain from upstream to downstream. Keywords: data envelopment analysis, fertilizer, state-owned enterprise, fertilizer producers